Large-Area Fluorescence and Electron Microscopic Correlative Imaging With Multibeam Scanning Electron Microscopy - Shibata, Shinsuke; Iseda, Taro; Mitsuhashi, Takayuki; Oka, Atsushi; Shindo, Tomoko; Moritoki, Nobuko; Nagai, Toshihiro; Otsubo, Shinya; Inoue, Takashi; Sasaki, Erika; Akazawa, Chihiro; Takahashi, Takao; et al. (Frontiers in Neural Circuits, 2019)
Recent improvements in correlative light and electron microscopy (CLEM) technology have led to dramatic improvements in the ability to observe tissues and cells. Fluorescence labeling has been used to visualize the localization of molecules of interest through immunostaining or genetic modification strategies for the identification of the molecular signatures of biological specimens. Newer technologies such as tissue clearing have expanded the field of observation available for fluorescence labeling; however, the area of correlative observation available for electron microscopy remains restricted. In this study, we developed a large-area CLEM imaging procedure to show specific molecular localization in large-scale electron microscopy (EM) sections of mouse and marmoset brain. Target molecules were labeled with antibodies and sequentially visualized in cryostat sections using fluorescence and gold particles. Fluorescence images were obtained by light microscopy immediately after antibody staining. Immunostained sections were postfixed for EM, and silver-enhanced sections were dehydrated in a graded ethanol series and embedded in resin. Ultrathin sections for EM were prepared from fully polymerized resin blocks, collected on silicon wafers, and observed by multibeam scanning electron microscopy. Multibeam scanning electron microscopy has made rapid, large-area observation at high resolution possible, paving the way for the analysis of detailed structures using the CLEM approach. Here, we describe detailed methods for large-area CLEM in various tissues of both rodents and primates.